2020
DOI: 10.1159/000504524
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of NT-Pro-Brain Natriuretic Peptide for Risk of Pneumonia in Patients on Maintenance Hemodialysis

Abstract: Background/Aims: Pneumonia is a common type of infection in maintenance hemodialysis (MHD) patients, while the treatment and prevention progress still keep limited. N-terminal-pro-brain natriuretic peptide (NT-proBNP) is an important marker in reflecting cardiac failure which also is a risk factor for pneumonia. This study aimed to determine the possible predictive value of NT-proBNP for pneumonia in MHD patients. Methods: In this prospective study, the basic information of 276 MHD patients was collected in Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…β2-MG is concerned with the presentation and stabilization of major histocompatibility complex (MHC) I antigen on the cell surface, which is important in adjusting antigen presentation and immunity [31] . It has been reported that β2-MG is an independent predictor of pulmonary infection in hemodialysis patients [32] , which was found increased in 9 of the 10 patients we reported, consistently. With the progress of treatment and the remission of conditions, β2-MG got back into normal range, and during this remission β2-MG showed positive moderate rank correlation to the CRP and PCT, which were signi cantly correlated to the disease severity as well.…”
Section: Discussionsupporting
confidence: 84%
“…β2-MG is concerned with the presentation and stabilization of major histocompatibility complex (MHC) I antigen on the cell surface, which is important in adjusting antigen presentation and immunity [31] . It has been reported that β2-MG is an independent predictor of pulmonary infection in hemodialysis patients [32] , which was found increased in 9 of the 10 patients we reported, consistently. With the progress of treatment and the remission of conditions, β2-MG got back into normal range, and during this remission β2-MG showed positive moderate rank correlation to the CRP and PCT, which were signi cantly correlated to the disease severity as well.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, SRA1 upregulation exhibited a significant potential in diagnosing CHF patients, demonstrating high sensitivity and specificity in differentiating CHF patients from healthy individuals. Abnormal BNP levels, LAD, LVDd, and rLVEF volume are established diagnostic markers of CHF, and these parameters correspond to other pathogenetic factors, including respiratory failure, pneumonia, and chronic kidney dysfunction [ 22 , 23 , 24 , 25 , 26 ]. Additionally, a previous study demonstrated BNP and LVEF could predict the appropriate therapy and hospitalization in HF patients receiving internal cardioverter defibrillator (ICD) and identified a novel protein, soluble growth stimulation expression gene 2 protein (ST2) as a biomarker for the therapeutic efficiency of ICD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP is an inactive byproduct of proBNP cleavage that occurs under high filling pressures [17]. It remains stable at room temperature and increases to a higher level in pathological conditions [18,19]. Previous studies suggested that the serum NT-proBNP concentration could reflect the severity of right ventricular function injury, with a higher NT-proBNP level indicating a more severe CTEPH classification [20][21][22].…”
Section: Discussionmentioning
confidence: 99%